Young innovative companies: The new high-growth firms? - Dirk Czarnitzki; Julie Delanote (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Young Innovative Companies (YIC) gained increasing attention from governments and scholars due to their expected high innovative performance and growth. Consequently, this study investigates whether Young Innovative Companies, as defined by the EU, grow more than other firms, both in terms of employment and in terms of sales. Using a database of Flemish firms over the years 2001-2008 reveals that these firms do grow significantly more than other firms. In addition, this study shows that YICs can be differentiated from New Technology Based Firms and small young firms in terms of growth, pointing to the importance of combining the individual properties characterizing YICs, that is being young (<6 years), small (<250 employees) and R&D intensive (R&D intensity > 15%). In our estimations, we also take the underlying distribution of the growth variables into account by performing quantile regressions. The results of these quantile regressions reveal that YICs especially grow faster than the other, already fast-growing firms, indicating that they are high performers. In addition, we never find that these companies perform significantly worse than the other firms.
Keywords: M13; L25; O33; 330; Young Innovative Companies; Growth; Unternehmensgründung; Innovation; Unternehmenswachstum; Schätzung; Flämisch-Brabant